An analysis on the service dimensions of National Youth Skills Training Institutes via an integrated multi-attribute decision-making procedure - Anath Rau Krishnan,; Maznah Mat Kasim,; Suddin Lada,; Minah Japang, (Penerbit Universiti Kebangsaan Malaysia, 2021)
It is indeed a challenging undertaking for the key players of Malaysian National Youth Skills Training Institutes (IKBNs, in Malay) to decide the finest possible strategies that could significantly enhance their students’ satisfaction over their services. It involves the consideration of various service attributes that naturally carry diverse priorities. Therefore, this study aimed at recommending some efficient strategies to improve student satisfaction in IKBNs by systematically uncovering the relative priorities of service dimensions. In this study, we carried out a Delphi survey involving a group of experts to validate the list of service attributes elicited from past literature. A questionnaire, which was designed based on the finalised 41 attributes, was then used to gather the necessary data from a sample of 636 IKBN students. With the help of factor analysis, these 41 attributes were then grouped into nine independent dimensions. Further analysis using the group-based compromised analytical hierarchy process (C-AHP) has identified training tools, training delivery, tangible amenities, student-centred management, and training instructors as the five most salient dimensions of student satisfaction. trastudy could enable the IKBNs to manage their resource better when improving their services. From the management science perspective, this study has contributed a new hybrid multi-attribute decision-making procedure combining Delphi survey, factor analysis, and group C-AHP. The procedure is appropriate for dealing with any complex decision problems that entail a large set of evaluation attributes.